Under the shadow of emergency : examining the legality and implication of Ethiopia’s state of emergency laws on human rights - Ashagrey, Henok (University of Pretoria, 2024)
Mini Dissertation (LLM (Human rights and Democratization in Africa))--University of Pretoria, 2024.